Polyarticular Septic Arthritis Caused by Haemophilus Influenzae in an Asplenic Patient: A Case Report - Roberto Desarden; Roya Caloia (Clinical Practice and Cases in Emergency Medicine)
Introduction: Prevalence of serious infections from Haemophilus influenzae has diminished over the last few decades because of immunizations against the most virulent serotype. However, over the last few years a handful of septic arthritis cases secondary to H influenzae have been documented. Most of the cases documented are in the pediatric and unimmunized population. This is a case of polyarticular septic arthritis in a 69-year-old male who presented with syncope and ankle pain. Case report: A 69-year-old male presented to the emergency department after a syncopal event at home and complaining of right ankle pain. He was tachycardic and tachypneic on presentation and had an erythematous painful right ankle and right elbow. Aspiration of both joints produced purulent aspirate that grew H influenzae. Antibiotics were started, and the patient was taken to the operating room for emergent joint lavage. The patient made a full recovery and was discharged home with a peripherally inserted central catheter line for continued intravenous (IV) antibiotics. Conclusion: Our case highlights an atypical presentation for a case of polyarticular septic arthritis caused by H influenzae. We were unable to rule out endocarditis as a source of the bacterial seeding, and the patient improved with IV antibiotics and surgical lavage of the affected joints.